2016
DOI: 10.3109/1354750x.2016.1153722
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases as candidate biomarkers in adults with congenital heart disease

Abstract: Context Matrix metalloproteinases (MMPs) are associated with diastolic dysfunction and heart failure in acquired heart disease. Objective To investigate the role of MMPs as novel biomarkers in clinically stable adults with congenital heart disease. Methods We measured serum MMP-2, -3, -9 and tissue inhibitor of matrix metalloproteinase-1 in 425 patients and analysed the association with cardiac function and exercise capacity. Results MMP-2 was significantly associated with exercise capacity, ventilatory effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…10 Thus, the patients' volume status was optimized before the procedure, which might have impacted the predictive value of baseline BNP levels. In particular, the stability of Gal-3 and ST2 is consistent, also with respect to differences in loading conditions, and is less affected by volume status 17,23,24,29 ; the fact that the predictive value of the fibrotic biomarkers ST2 and Gal-3 was also more pronounced than BNP under these conditions confirms the diagnostic sensitivity of the fibrotic biomarkers examined in this study. In a recent trial, the predictive value of Gal-3 and ST2 for MR reduction after cardiac resynchronization therapy implantation in HF patients were analyzed.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…10 Thus, the patients' volume status was optimized before the procedure, which might have impacted the predictive value of baseline BNP levels. In particular, the stability of Gal-3 and ST2 is consistent, also with respect to differences in loading conditions, and is less affected by volume status 17,23,24,29 ; the fact that the predictive value of the fibrotic biomarkers ST2 and Gal-3 was also more pronounced than BNP under these conditions confirms the diagnostic sensitivity of the fibrotic biomarkers examined in this study. In a recent trial, the predictive value of Gal-3 and ST2 for MR reduction after cardiac resynchronization therapy implantation in HF patients were analyzed.…”
Section: Discussionsupporting
confidence: 78%
“…13,14 Increased cardiac collagen synthesis and impaired degradation in response to pressure and volume overload in patients with MR lead to an imbalance in collagen metabolism and contribute to collagen accumulation and consequently cardiac structural remodeling processes, myocardial stiffness, and fibrosis. [15][16][17] Galectin-3 (Gal-3), a member of the lectin family, and suppression of tumorigenicity 2 (ST2), a member of the interleukin-1 family, are synthesized and secreted in response to increased cardiac volume and pressure overload and enhanced myocardial wall stress. Gal-3 and ST2 induce fibrotic alterations and are upregulated in severe MR and LV dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MMP‐2 and MMP‐9 levels are elevated in patients with LV volume overload, which contributes to myocardial collagen accumulation and subsequent cardiac dysfunction. Further, both MMPs have predictive value regarding cardiovascular events, including mortality . Myocardial remodeling processes are also closely associated with inflammation processes, and published data have shown that extensive inflammation magnifies these cardiac structural alterations and thus may accelerate the progression of heart failure (HF) .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Increased cardiac collagen synthesis and impaired degradation in response to pressure and volume overload in patients with MR lead to an imbalance of collagen metabolism and contribute to collagen accumulation and consequently cardiac structural remodeling processes, myocardial stiffness, and fibrosis. [14][15][16] Matrix metalloproteinases (MMPs) are important regulators of ECM turnover and myocardial remodeling processes. [14][15][16] In particular, MMP-2 and MMP-9 levels are elevated in patients with LV volume overload, which contributes to myocardial collagen accumulation and subsequent cardiac dysfunction.…”
mentioning
confidence: 99%
See 1 more Smart Citation